The portrait of kuta village community economic activities and its application as the economic learning source based on the cultural values - Afriza, Edi Fitriana; Srigustini, Astri (Dinamika Pendidikan, 2016)
Education based on the local culture as the form of local wisdom would be better to form the character and develop studentsâ potentials than education based on the foreign cultures. The objective of the study was to improve studentsâ knowledge and understanding on the pattern development of economic activity at the community who retained its local wisdom. Kuta village is located at Karangpaningal Village, Tambaksari District, Ciamis Regency which is one of the traditional villages which maintains its traditions in harmony with nature. It was a qualitative study and the data were collected through interviews, observation, and literature study. The results of this study were: 1). There was a development of the communityâs livelihood at Kuta Village; 2) .The scope of economic activity was still in the micro scale; 3). There was a technological transformation in natural resource management. Then; it is recommended that the local wisdom was very suitable to be the subject materials in the form of narratives, stories, posters, or comics.